Class A CpG oligodeoxynucleotide inhibits IFN‐γ‐induced signaling and apoptosis in lung cancer - Shuhei Teranishi; Nobuaki Kobayashi; Seigo Katakura; Chisato Kamimaki; Sousuke Kubo; Yuji Shibata; Masaki Yamamoto; Makoto Kudo; Hongmei Piao; Takeshi Kaneko (Thoracic Cancer, 2020)
Abstract Background Currently, anticancer immunotherapy based on PD‐1/PD‐L1 blockade with immune checkpoint inhibitors (ICIs) is being used as a standard therapy for non‐small cell lung cancer (NSCLC). However, more effective treatments are required as these tumors are often resistant and refractory. Here, we aimed to determine the effects of immunomodulatory oligodeoxynucleotides (ODNs) in terms of the presence or absence of CpG motifs and the number of consecutive guanosines. Methods Western blots were used to measure the molecules which regulate the expression of PD‐L1 in human lung cancer cell lines after incubation with several cytokines and ODNs. The expression of PD‐L1 and β2‐microglobulin (β2‐MG) on A549 cells, and IFN‐γ‐induced apoptosis with ODNs were examined by flow cytometry. The relationship between IFN‐γ receptor and ODN was analyzed by ELISA and immunofluorescence chemistry. Results Our results verified that A‐CpG ODNs suppress the upregulation of IFN‐γ‐induced PD‐L1 and β2‐MG expression. In addition, we found that ODNs with six or more consecutive guanosines (ODNs with poly‐G sequences) may competitively inhibit the IFN‐γ receptor and abolish the effect of IFN‐γ, thereby suppressing apoptosis and indoleamine 2,3‐dioxygenase 1 expression in human lung cancer cells. The tumor microenvironment regulates whether this action will promote or suppress tumor immunity. Thus, in immunotherapy with CpG ODNs, it is essential to consider the effect of ODNs with poly‐G sequences. Conclusions This study suggests that ODNs containing six or more consecutive guanosines may inhibit the binding of IFN‐γ to IFN‐γ receptor. However, it does not directly show that ODNs containing six or more consecutive guanosines competitively inhibit the IFN‐γ receptor, and further studies are warranted to confirm this finding. Key points Significant findings of the study: Oligodeoxynucleotides with a contiguous sequence of six or more guanosines may competitively inhibit the IFN‐γ receptor and abolish the action of IFN‐γ. This may suppress IFN‐γ‐induced apoptosis and indoleamine‐2,3‐dioxygenase‐1 expression in human lung cancer cells. What this study adds: A‐CpG and poly‐G ODN may overcome tolerance if the cause of ICI tolerance is high IDO expression. However, IFN‐γ also has the effect of suppressing apoptosis of cancer cells, and it is necessary to identify the cause of resistance.